2016
DOI: 10.1186/s12889-016-3619-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in Brazil, 1998–2014: an ecological study

Abstract: BackgroundAttempted suicide is the main predictor of suicide constituting a major public health issue worldwide. It is estimated that for every completed suicide, 10 to 20 suicide attempts occur. Important part of the occurrences of suicide attempts in Brazil are registered in the hospital information system for coverage of more than 70 % allows to evaluate the extent of this problem in the country. The scope of this article is to analyse hospitalizations resulting from suicide attempts at public hospitals or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
2
18
0
2
Order By: Relevance
“…Male to female ratio was 2.14, resembling the supremacy of males for self-poisoning suicidal deaths. The predominance of men in self-poisoning drug related deaths had been reported by other investigators [5, 21, 27, 28]. Males often choose more violent suicide methods that will assure to reach their desired aim [2931].…”
Section: Discussionmentioning
confidence: 75%
“…Male to female ratio was 2.14, resembling the supremacy of males for self-poisoning suicidal deaths. The predominance of men in self-poisoning drug related deaths had been reported by other investigators [5, 21, 27, 28]. Males often choose more violent suicide methods that will assure to reach their desired aim [2931].…”
Section: Discussionmentioning
confidence: 75%
“…The Brazilian Hospital Information System reported that suicide attempts were responsible for 153,061 hospitalizations of people aged 10 years or over in the period 1998-2014, which indicates that such events were one of the main causes of hospitalization 9,22,23 . The situation is even more critical when one considers that it is estimated that out of every three suicide attempts, only one received attention from the health services 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Iran [22] and Pakistan [23] demonstrate that cases of attempted suicide are younger compared to victims of successful suicide. Generally, probability of success of suicide attempts rises by age; this finding can be due to more violent methods used by older attempters, their greater tendency for dying and their lower resistance to physical injuries caused by attempts [10,22,24].…”
Section: Discussionmentioning
confidence: 99%